The Relationship between Stunting and Motor Development in Children Aged 2-5 Years in the Tamalate Community Health Center Working Area - Latief, Shofiyah; Rahmatillah, Rahmatillah; Halifah D. L., Andi Millaty; Darma, Sidrah; Jafar, Muh. Alfian; Kartika, Andy Visi (Jurnal Biologi Tropis, 2024)
Stunting is a chronic nutritional condition resulting from a lack of nutritional intake from food that is not in accordance with nutritional needs based on the body length index for age, which results in less than optimal motor development. The aim of this study was to determine the relationship between stunting and the motor development of children aged 2-5 years at the Tamalate Community Health Center. The type of research is descriptive analytical research with a cross sectional research design. The sampling technique for the non-probability sampling method is Accidental Sampling. This study used 34 respondents as samples who met the inclusion criteria. This research instrument uses a microtoise stature meter for the stunting variable and the Denver Developmental Screening Test (DDST) for the motor development variable. The results of the study showed that the majority of respondents who experienced stunting were aged 24-36 months, with the same number of males and females, while non-stunted respondents were aged 37-48 months with the majority being male. The majority of stunting figures are short stature, 79.4% of children aged 2-5 years in the working area of the Tamalate Community Health Center. The description of motor development shows that the majority of respondents have normal motor function, however, 13.23% of stunted children are found to be suspected of having motor disorders, while only 4.41% of non-stunting children are found. In conclusion, there is a significant relationship between stunting and the motor development of children aged 2-5 years in the working area of the Tamalate Community Health Center.